A core-shell structure catalyst and a preparation method and application thereof
By using a core-shell structure catalyst with carbon balls as the core and titanium oxide Ti3O5 as the shell in magnesium-based hydrogen storage materials, the problem of poor kinetic performance of magnesium-based hydrogen storage alloys is solved, low-temperature dehydrogenation effect is achieved, and it is suitable for large-scale production.
Patent Information
- Application Number
- CN202511056857.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-24
- Estimated Expiration
- 2045-07-30
AI Technical Summary
The existing magnesium-based hydrogen storage alloys have poor kinetic properties. Even after adding catalysts such as carbon nanotubes, the dehydrogenation temperature is still higher than 300°C. In addition, the synthesis process is complex and costly, making it unsuitable for large-scale production.
A core-shell structure catalyst with carbon spheres as the core and titanium oxide Ti3O5 as the shell is used. Titanium oxide is coated on the surface of the carbon spheres through a preparation method to form a Ti3O5@CS core-shell structure catalyst, which is used for magnesium-based hydrogen storage materials.
Significantly reduce the dehydrogenation temperature of magnesium-based hydrogen storage materials below 300°C, enhance the catalytic effect of the catalyst, and improve the hydrogen desorption performance of magnesium-based hydrogen storage materials.
Smart Images

Figure CN120550794B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of catalysts, in particular to a core-shell structure catalyst and a preparation method and application thereof. BACKGROUND
[0002] Magnesium-based hydrogen storage materials are considered to be one of the most promising metal hydrogen storage materials due to their large hydrogen storage capacity, abundant resources and low cost. However, the kinetic performance of magnesium-based hydrogen storage alloys is poor, and the addition of catalysts can effectively reduce the hydrogen desorption energy barrier, significantly reduce the hydrogen release temperature and enhance the kinetic performance. However, most high-performance catalysts such as carbon nanotubes and graphene have complex synthesis processes and expensive raw materials, which do not have the potential for large-scale production. Moreover, the dehydrogenation temperature of the modified magnesium-based hydrogen storage alloy after adding the above catalysts is still higher than 300℃. SUMMARY
[0003] The present application provides a core-shell structure catalyst and a preparation method and application thereof. The core-shell structure catalyst takes carbon spheres as the core and titanium oxide as the shell, and can significantly reduce the dehydrogenation temperature of magnesium-based hydrogen storage materials, so that the dehydrogenation temperature is lower than 300℃.
[0004] The present application is achieved in the following manner:
[0005] In a first aspect, the present application provides a core-shell structure catalyst, which comprises:
[0006] a core, the core comprising carbon spheres; and
[0007] a shell, the shell being coated on the surface of the core, the shell being titanium oxide, and the titanium oxide being Ti3O5.
[0008] In a second aspect, the present application provides a preparation method of the core-shell structure catalyst of the first aspect, which comprises the following steps:
[0009] preparing carbon spheres;
[0010] mixing and impregnating the carbon spheres with a titanium n-propyl alcohol solution, and then evaporating to obtain an impregnated product; the concentration of the titanium n-propyl alcohol solution is 0.3-0.5 mol / L;
[0011] placing the impregnated product in a nitrogen or inert atmosphere, and heating to 700-900℃ at a rate of 3-5℃ / min, and then heating to 1100℃ at a rate of 4-6℃ / min for reaction, and then cooling to obtain a Ti3O5@CS core-shell structure catalyst.
[0012] In a third aspect, the present application provides an application of the core-shell structure catalyst prepared by the preparation method of the core-shell structure catalyst of the first aspect or the second aspect in the preparation of magnesium-based hydrogen storage materials.
[0013] This application has at least the following beneficial effects:
[0014] The core-shell structure catalyst of the present application has a carbon ball as the core and a Ti3O5 as the shell. The carbon ball has a high surface area, specific surface area, active electronic properties, and has a good catalytic effect; the Ti3O5 in the shell has a large number of transition metals in a valence state. During the catalytic process, the multivalent environment is conducive to the exchange and transfer of electrons, which can accelerate the diffusion of atoms. The low stability and many structural defects are conducive to the hydrogen storage reaction, making the core-shell structure catalyst have a good catalytic effect, effectively increasing the hydrogen release temperature of the magnesium-based hydrogen storage material, and making the dehydrogenation temperature lower than 300°C.
[0015] The preparation method of the core-shell structure catalyst of the present application can effectively coat titanium oxide on the surface of carbon spheres to form a core-shell structure catalyst with carbon spheres as the core and titanium oxide as the shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 The SEM images of the carbon nanospheres of Examples 1 to 4 of the present application are as follows;
[0018] Figure 2 SEM images of the Ti3O5@CS core-shell structure catalysts of Examples 1, 5, and 7 of the present application;
[0019] Figure 3 This is the XRD pattern of the Ti3O5@CS core-shell structure catalyst of Example 1 of the present application;
[0020] Figure 4 This is an energy spectrum analysis (EDS) diagram of the Ti3O5@CS core-shell structure catalyst of Example 1 of the present application;
[0021] Figure 5 This is the SEM image of the TiO2@CS core-shell structure catalyst of Examples 8 to 11 of the present application;
[0022] Figure 6 This is the XRD pattern of the TiO2@CS core-shell structure catalyst of Example 8 of the present application;
[0023] Figure 7 Energy dispersive spectrometry (EDS) analysis of the TiO2@CS core-shell structure catalyst of Example 8 of the present application;
[0024] Figure 8 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg 41 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg
[0025] Figure 9 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg 41 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg
[0026] Figure 10 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg 41 The temperature-variable hydrogen release test graph of the composite material of the different ratio of the nanometer carbon sphere of Example 1 of the present application and Sm5Mg DETAILED DESCRIPTION
[0027] The embodiments of the present application will be described in detail below with examples, but those skilled in the art will understand that the following examples are only for illustration of the present application and should not be regarded as limiting the scope of the present application. The specific conditions are not specified in the examples, and the conventional conditions or the conditions recommended by the manufacturer are used. The reagents or instruments used are not specified by the manufacturer, and are conventional products that can be purchased on the market.
[0028] The following will specifically describe one kind of core-shell structure catalyst and its preparation method according to the embodiments of the present application:
[0029] In a first aspect, the present application provides a core-shell structure catalyst, which comprises an inner core and an outer shell, wherein the inner core comprises a carbon sphere; the outer shell is coated on the surface of the inner core, and the outer shell is a titanium oxide, and the titanium oxide is Ti3O5.
[0030] Exemplarily, the size of the carbon sphere is 200-400 nm, for example, any one of 200 nm, 250 nm, 300 nm, 350 nm and 400 nm or a value between any two of them. The outer shell comprises a plurality of particulate titanium oxides, and a large number of particulate titanium oxides are coated on the outer surface of the carbon sphere to form the outer shell. Exemplarily, the size of the titanium oxide is 10-30 nm, for example, any one of 10 nm, 15 nm, 20 nm, 25 nm and 30 nm or a value between any two of them.
[0031] In a second aspect, the present application provides a preparation method of the above-mentioned core-shell structure catalyst, which comprises the following steps:
[0032] (1) A carbon sphere is prepared.
[0033] The preparation steps of the exemplary carbon spheres include: configuring a glucose solution, performing a hydrothermal carbonization reaction on the glucose solution, then performing cleaning, obtaining a solid powder, and performing drying, then placing the dried solid powder in a nitrogen or inert atmosphere and heating at 3-5℃ / min to 800-900℃, then heating at 4-6℃ / min to 1000-1200℃, and obtaining carbon spheres after cooling.
[0034] In some embodiments, the dried solid powder is placed in a nitrogen or inert atmosphere and heated at 3-5℃ / min to 800℃, then heated at 4-6℃ / min to 1100℃ for 1-10h, and carbon spheres are obtained after cooling. This method can remove oxygen elements in the carbon spheres.
[0035] Illustratively, the heating rate to 800℃ is 3℃ / min, 4℃ / min, or 5℃ / min; and the heating rate to 1100℃ is 4℃ / min, 5℃ / min, or 6℃ / min.
[0036] In some embodiments, the step of performing a hydrothermal carbonization reaction on the glucose solution includes: hydrothermal reaction of a glucose solution with a concentration of 1-10mol / L at a temperature of 180-220℃ for 3-6 hours.
[0037] Illustratively, the concentration of the glucose solution is 1mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, or 10mol / L. The temperature of the hydrothermal reaction is 180℃, 190℃, 200℃, 210℃, or 220℃. The time of the hydrothermal reaction is 3h, 4h, 5h, or 6h.
[0038] When the glucose solution is cleaned after the hydrothermal carbonization reaction, the solid powder obtained is dried at a temperature of 55-65℃, for example, the drying temperature is 55℃, 60℃, or 65℃.
[0039] (2) The carbon spheres are mixed and immersed with a titanium n-propyl alcohol solution to obtain an impregnated product after evaporation. The concentration of the titanium n-propyl alcohol solution is 0.3-0.5mol / L;
[0040] Illustratively, the concentration of the titanium n-propyl alcohol solution is 0.3mol / L, 0.4mol / L, or 0.5mol / L.
[0041] Illustratively, the temperature condition for immersion is 70-100℃, for example, 70℃, 80℃, 90℃, or 100℃.
[0042] (3) The impregnated product is placed in a nitrogen or inert atmosphere, and heated to 700-900℃ at a rate of 3-5℃ / min, and then heated to 1100℃ at a rate of 4-6℃ / min to react, and after cooling, the Ti3O5@CS core-shell structure catalyst is obtained.
[0043] In an embodiment, the heating is performed at a rate of 4℃ / min to 700-900℃, and then at a rate of 5℃ / min to 1100℃, and the temperature is maintained for 1-2h. For example, the heating is performed at a rate of 4℃ / min to 700℃, 800℃ or 900℃.
[0044] Further, in a possible embodiment, the method further comprises: placing the Ti3O5@CS core-shell structure catalyst in a nitrogen or inert atmosphere, and heating to 700-770℃ at a rate of 4-6℃ / min to react, and after cooling, the TiO2@CS core-shell structure catalyst is obtained.
[0045] Illustratively, the heating rate to 700-770℃ is 4℃ / min, 5℃ / min or 6℃ / min. Alternatively, the heating is performed at a rate of 4-6℃ / min to 700℃, 720℃, 740℃, 750℃ or 770℃.
[0046] The method for preparing the core-shell structure catalyst of the present application can effectively coat titanium oxide on the surface of the carbon sphere to form a core-shell structure catalyst with the carbon sphere as the inner core and titanium oxide as the outer shell.
[0047] In a third aspect, the present application provides a use of the core-shell structure catalyst prepared by the method of the first aspect or the second aspect in preparing a magnesium-based hydrogen storage material.
[0048] The core-shell structure catalyst of the present application has the carbon sphere as the inner core and Ti3O5 as the outer shell. The carbon sphere has a high surface area, a high specific surface area and active electronic properties, and has good catalytic effect. The outer shell of titanium oxide has a large number of transition metals in valence state, and the multi-valence state environment is conducive to the exchange and transfer of electrons in the catalytic process, which can accelerate the diffusion of atoms, and the characteristics of low stability and many structural defects are conducive to the hydrogen storage reaction, so that the core-shell structure catalyst has good catalytic effect, effectively improves the hydrogen release temperature of the magnesium-based hydrogen storage material, and makes the dehydrogenation temperature lower than 300℃.
[0049] Among them, titanium pentoxide (Ti3O5) as a non-stoichiometric titanium oxide, shows unique catalytic performance in hydrogen absorption and release reaction, and its mechanism is mainly related to the variable valence characteristics of titanium, oxygen vacancy defects and surface active sites.
[0050] (1) Titanium pentoxide exists in Ti 3+ and Ti 4+Mixed valence, which can promote the dissociation and recombination of hydrogen molecules through redox cycles, is the key to catalytic activity. (2) Non-stoichiometric ratio leads to the existence of oxygen vacancies in the lattice, which can act as adsorption sites for hydrogen atoms, reduce the H2 dissociation energy barrier, and accelerate hydrogen diffusion. (3) Partially reduced Ti3O5 has certain electronic conductivity, which is beneficial to the charge transfer process and promotes hydrogen oxidation or reduction reactions.
[0051] Catalytic mechanism of Ti3O5@CS core-shell structure catalyst in hydrogen absorption and desorption reactions:
[0052] (1) Ti3O5 surface Ti 3+ sites provide unpaired electrons that interact with the σ antibonding orbital of H2, weakening the H-H bond and allowing it to dissociate into active hydrogen atoms (H), and oxygen vacancies further stabilize the adsorbed H. (2) Oxygen vacancies and lattice gaps provide migration channels for hydrogen atoms, which can form Ti-H bonds or O-H bonds with adjacent oxygen, achieving temporary hydrogen storage. In the hydrogen desorption process, the breaking of these bonds releases H2 through reverse reactions. (3) Ti3O5@CS core-shell structure catalyst formed by compounding Ti3O5 on carbon spheres (CS) can significantly improve its catalytic performance in hydrogen absorption and desorption reactions. Carbon spheres, as carriers, usually have abundant mesoporous / microporous structures that can disperse Ti3O5 nanoparticles, preventing their agglomeration and thus exposing more active sites (such as Ti 3+ and oxygen vacancies); the high conductivity of carbon spheres promotes the rapid transfer of electrons between Ti3O5 and the carrier, accelerating the hydrogen oxidation-reduction reaction. Ti3O5 surface Ti 3+ sites and oxygen vacancies directly dissociate H2 into active hydrogen atoms (H), and defect sites on the surface of carbon spheres can further adsorb H2 and promote the breaking of H-H bonds through electron transfer. Dissociated H on Ti3O5 can migrate to the surface of carbon spheres, which act as "hydrogen storage reservoirs" to temporarily accommodate hydrogen atoms, alleviating the hydrogen saturation problem on the surface of Ti3O5. By controlling the particle size of Ti3O5 to increase the interfacial contact area between Ti3O5 and carbon spheres, their interaction is increased. The porous structure of carbon spheres provides a fast diffusion path for hydrogen atoms, reducing the bulk diffusion resistance. The conductivity of carbon spheres helps Ti3O5 quickly transfer electrons (such as 2H + + 2e - →H2) during hydrogen desorption, avoiding kinetic lag caused by local charge accumulation. The high thermal conductivity of carbon spheres helps to evenly distribute the reaction heat, avoiding local overheating that can cause catalyst deactivation.
[0053] The following examples further describe the core-shell structure catalyst, its preparation method, and application. Examples
[0054] The embodiment provides a preparation method of a core-shell structure catalyst, which comprises the following steps.
[0055] Preparation of the nanocarbon sphere:
[0056] 1) A 3 mol / L glucose solution is prepared, and after being uniformly stirred, the solution is placed in a polytetrafluoroethylene-lined hydrothermal reaction kettle to be hydrothermally reacted at 200 DEG C for 4 hours;
[0057] 2) After being naturally cooled to room temperature, the solution is taken out, and is centrifuged twice with ethanol and deionized water respectively, and the obtained solid powder is dried in an oven at 60 DEG C overnight;
[0058] 3) In a tube furnace, the temperature is first raised to 800 DEG C at a rate of 4 DEG C / min, and then raised to 1100 DEG C at a rate of 5 DEG C / min and kept for 2 hours, and the nanocarbon sphere is obtained after being naturally cooled.
[0059] 4) A 0.1 mol / L titanium n-propylate solution is prepared, 1 g of the nanocarbon sphere is placed in the prepared titanium n-propylate solution, and is stirred and immersed at 80 DEG C for half an hour to be evaporated, so that an impregnated product is obtained;
[0060] 5) The impregnated product is taken out and placed in a tube furnace, and the temperature is first raised to 800 DEG C at a rate of 4 DEG C / min, and then raised to 1100 DEG C at a rate of 5 DEG C / min and kept for 1 hour.
[0061] 6) The product Ti3O5@CS catalyst is obtained after being naturally cooled.
[0062] Embodiments 2 to 4
[0063] Embodiments 2 to 4 all provide a preparation method of a core-shell structure catalyst, and the difference from the embodiment 1 is that the concentration of the glucose solution in the embodiments 2 to 4 is 5 mol / L, 10 mol / L and 15 mol / L respectively.
[0064] Embodiments 5 to 7
[0065] Embodiments 5 to 7 all provide a preparation method of a core-shell structure catalyst, and the difference from the embodiment 1 is that the concentration of the titanium n-propylate solution in the embodiments 5 to 8 is 0.2 mol / L, 0.3 mol / L and 0.5 mol / L respectively. Embodiment
[0066] The embodiment provides a preparation method of a core-shell structure catalyst, and the difference from the embodiment 1 is that step 7) is added, that is, the Ti3O5@CS core-shell structure catalyst is placed in a tube furnace, the temperature is raised to 750 DEG C at a rate of 5 DEG C / min, and the product TiO2@CS catalyst is obtained after being naturally cooled.
[0067] Example 9 to Example 11
[0068] Examples 9 to 11 all provide a method for preparing a core-shell structure catalyst, which differs from Example 8 only in that the n-propoxide titanium solution in Examples 9 to 11 is 0.2 mol / L, 0.3 mol / L, and 0.5 mol / L, respectively.
[0069] Test Example 1
[0070] (1) The carbon nanospheres prepared in Examples 1 to 4 were observed under an electron scanning microscope, and the SEM images were as follows: Figure 1 As shown in (a), (b), (c), and (d).
[0071] from Figure 1 As can be seen from (a), (b), (c), and (d), the carbon spheres prepared in Examples 1 to 4 are all spherical with good roundness and nanometer size.
[0072] (2) The Ti3O5@CS core-shell structure catalysts prepared in Example 1 and Example 5 to Example 7 were observed under an electron scanning microscope, and the SEM images obtained were as follows: Figure 2 As shown in (a), (b), (c), and (d).
[0073] from Figure 2 It can be seen from (a), (b), (c), and (d) that the Ti3O5@CS core-shell structure catalysts prepared in Examples 1 and 5 to 7 are spherical, with the core being nanocarbon balls and the surface being particles loaded on the surface of the nanocarbon balls. The surface loading of the core-shell structure catalyst is good.
[0074] (3) The Ti3O5@CS core-shell structure catalyst prepared in Example 1 was subjected to XRD detection, and the obtained XRD pattern was as follows: Figure 3 As shown. Figure 3 It can be seen from the XRD pattern that there is a characteristic peak of Ti3O5, which shows that the catalyst prepared in Example 1 contains Ti3O5.
[0075] (4) The Ti3O5@CS core-shell structure catalyst prepared in Example 1 was tested by photoelectron spectroscopy. The results are as follows: Figure 4 As shown. Figure 4 It can be seen from the figure that the catalyst of Example 1 contains C, Ti and O, and the elements are evenly distributed.
[0076] Test Example 2
[0077] (1) The TiO2@CS core-shell structure catalysts prepared in Examples 8 to 11 were observed under an electron scanning microscope, and the SEM images obtained were as follows: Figure 5(a), (b), (c), (d) in the figure.
[0078] From Figure 5 (a), (b), (c), (d) in the figure, it can be seen that the TiO2@CS core-shell structure catalyst prepared in examples 8~11 is spherical, the inner core is a nanocarbon sphere, and the surface is a particle loaded on the surface of the nanocarbon sphere. The core-shell structure catalyst is well loaded on the surface.
[0079] (2) The TiO2@CS core-shell structure catalyst prepared in example 8 was subjected to XRD detection, and the obtained XRD graph is shown in Figure 6 From Figure 6 the figure, it can be seen that the XRD graph has a characteristic peak of TiO2, which indicates that the catalyst prepared in example 1 contains TiO2.
[0080] (3) The TiO2@CS core-shell structure catalyst prepared in example 8 was subjected to photoelectron spectroscopy detection, and the results are shown in Figure 7 From Figure 7 the figure, it can be seen that the catalyst of example 8 contains C, Ti and O, and the element distribution is uniform.
[0081] Test example 3
[0082] (1) The nanocarbon spheres prepared in example 1 were mixed with Sm5Mg 41 alloy powder at a ratio of 1wt%, 3wt%, 5wt% and 7wt% respectively, and then ball-milled to obtain a composite material. The variable-temperature hydrogen release test of the composite material was carried out, and the results are shown in Figure 8 .
[0083] From Figure 8 the results, it can be seen that the addition of 5wt% of carbon spheres can reduce the hydrogen release temperature of the composite material to 267 degrees.
[0084] (2) The Ti3O5@CS core-shell structure catalyst prepared in examples 1 and 5~7 was mixed with Sm5Mg 41 alloy powder at a ratio of 5wt%, and then ball-milled to obtain a composite material. The variable-temperature hydrogen release test of the composite material was carried out, and the results are shown in Figure 9 .
[0085] From Figure 9 the results, it can be seen that the Ti3O5@CS core-shell structure catalyst prepared in the application is used for Sm5Mg 41 composite material, which can reduce the hydrogen release temperature to 300℃; when the concentration of titanium n-propyl alcohol is 0.5mol / L, the Ti3O5@CS core-shell structure catalyst is used for Sm5Mg 41The composite material can reduce the dehydrogenation temperature to 262 ° C; when the concentration of titanium n-propoxide is 0.3 mol / L, the prepared Ti3O5@CS is used as a core-shell structure catalyst for Sm5Mg 41 The composite material can reduce the hydrogen desorption temperature to 263°C.
[0086] (3) The TiO2@CS core-shell structure catalysts prepared in Examples 8 to 11 were mixed with Sm5Mg 41 The alloy powders were mixed and ball milled to obtain a composite material. The composite material was subjected to a temperature-dependent hydrogen release test. The results are as follows: Figure 10 shown.
[0087] from Figure 10 The results show that the TiO2@CS core-shell structure catalyst prepared in the embodiment of the present application is used for Sm5Mg 41 The composite material can reduce the dehydrogenation temperature to 264 ° C or below. The TiO2@CS core-shell structure catalyst prepared in Example 8 is used for Sm5Mg 41 The composite material can reduce the dehydrogenation temperature to a minimum of 264 ° C. In Example 9, the TiO2@CS core-shell structure catalyst was prepared for Sm5Mg 41 The composite material can reduce the dehydrogenation temperature to a minimum of 247 ° C. In Example 10, the TiO2@CS core-shell structure catalyst was prepared for Sm5Mg 41 The composite material can reduce the dehydrogenation temperature to a minimum of 249 ° C. In Example 10, the TiO2@CS core-shell structure catalyst was prepared for Sm5Mg 41 The composite material can reduce the hydrogen desorption temperature to as low as 245°C.
[0088] The above are merely specific embodiments of the present application and are not intended to limit the present application. Those skilled in the art will readily appreciate that various modifications and variations are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present application shall be included within the scope of protection of the present application.
Claims
1. A method for preparing a core-shell structured catalyst, characterized by, The core-shell structure catalyst comprises an inner core and an outer shell, the inner core comprises carbon spheres; the outer shell is coated on the surface of the inner core, the outer shell is titanium oxide, and the titanium oxide is Ti3O5; the preparation method comprises the following steps: carbon spheres are prepared; the carbon spheres are mixed with a titanium n-propyl alcohol solution for impregnation and then evaporated to obtain an impregnation product; the concentration of the titanium n-propyl alcohol solution is 0.3-0.5 mol / L; the impregnation product is placed in a nitrogen or inert atmosphere, heated to 700-900 ℃ at a rate of 3-5 ℃ / min, and then heated to 1100 ℃ at a rate of 4-6 ℃ / min for reaction, and then cooled to obtain a Ti3O5@CS core-shell structure catalyst.
2. The method for preparing a core-shell structure catalyst according to claim 1, wherein: The size of the carbon spheres is 200-400 nm, and the outer shell comprises a plurality of granular titanium oxides, and the size of the granular titanium oxides is 10-30 nm.
3. The method for preparing a core-shell structure catalyst according to claim 2, wherein: The preparation step of the carbon spheres comprises: a glucose solution is prepared, the glucose solution is subjected to a hydrothermal carbonization reaction, then washed, solid powder is obtained and dried, then the dried solid powder is placed in a nitrogen or inert atmosphere and heated to 800-900 ℃ at a rate of 3-5 ℃ / min, and then heated to 1000-1200 ℃ at a rate of 4-6 ℃ / min, and then cooled to obtain the carbon spheres.
4. The method of claim 3, wherein the core-shell structured catalyst is prepared by the steps of: The step of subjecting the glucose solution to a hydrothermal carbonization reaction comprises: hydrothermal reaction of a glucose solution with a concentration of 1-10 mol / L at a temperature of 180-220 ℃ for 3-6 hours.
5. The method for preparing a core-shell structure catalyst according to claim 1, wherein: The carbon spheres are mixed with the titanium n-propyl alcohol solution for impregnation at a temperature of 70-100 ℃.
6. Use of a core-shell structure catalyst prepared by the preparation method of any one of claims 1-5 in preparation of a magnesium-based hydrogen storage material.
Citation Information
Patent Citations
Dehydrogenation catalyst as well as preparation method and application thereof
CN119500205A